Optimising facility management in the South African National Defence Force through advanced gis solutions: a case of the Faculty of Military Science - Nyembe, Sipokuhle (Stellenbosch : Stellenbosch University, 2026)
Thesis (MMil)--Stellenbosch University, 2026.